Effect of Rodent Control Program on Incidence of Zoonotic Cutaneous Leishmaniasis, Iran - Abdoli, Amir; Mazaherifar, Samaneh; Solhjoo, Kavous; Zargar, Mohsen Farhang; Jahromi, Hayedeh Parvin; Taghipour, Ali; Darayesh, Mohammad; Badri, Milad; Pirestani, Majid; Falahi, Shahab; Kenarkoohi, Azra (Emerging infectious diseases, 2024)
We report the effect of a rodent control program on the incidence of zoonotic cutaneous leishmaniasis in an endemic region of Iran. A 1-year interruption in rodent control led to 2 years of increased incidence of zoonotic cutaneous leishmaniasis. Restarting rodent control led to a decline of zoonotic cutaneous leishmaniasis.